Putting On and Taking Off the Capulana: A Grounded Theory of How Mozambican Women Manage Gender Oppression - Laura Nicole Tomm-Bonde; Rita Schreiber; Marjorie MacDonald (SAGE Publishing, 2021)
Gender-based oppression is a pervasive global challenge, but has taken a back seat to other issues in Mozambique. The purpose of this grounded theory study was to explore how Mozambican women manage multiple oppressions in their lives in the context of the AIDS epidemic. Using interviews, documents, and constant comparison, we constructed a theory, Putting on and Taking Off the Capulana, to explain how women are socialized into and push back against the prevailing societal misogyny. The theory comprises four categories: Putting on the Capulana, Turning a Blind Eye, Playing the Game, and Taking Off the Capulana. Women adopt sex-role expectations, becoming socialized into patriarchal society. They are silent about their oppression, and society colludes in this. They use a strategic process to gain a sense of control over their situations. Finally, some women develop a critical consciousness and are able to resist their oppression in emancipatory ways.